2014
DOI: 10.1007/s00401-014-1281-3
|View full text |Cite
|
Sign up to set email alerts
|

Premature termination of SMARCB1 translation may be followed by reinitiation in schwannomatosis-associated schwannomas, but results in absence of SMARCB1 expression in rhabdoid tumors

Abstract: In schwannomatosis, germline SMARCB1 mutations predispose to the development of multiple schwannomas, but not vestibular schwannomas. Many of these are missense or splice-site mutations or in-frame deletions, which are presumed to result in the synthesis of altered SMARCB1 proteins. However, also nonsense and frameshift mutations, which are characteristic for rhabdoid tumors and are predicted to result in the absence of SMARCB1 protein via nonsense-mediated mRNA decay, have been reported in schwannomatosis pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…In accord with this postulate are the findings of Hulsebos et al (2014a). These authors analysed four schwannomatosis-associated SMARCB1 mutations that were located in the 5′ region of the gene and were predicted to introduce a premature translational termination codon (PTC).…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…In accord with this postulate are the findings of Hulsebos et al (2014a). These authors analysed four schwannomatosis-associated SMARCB1 mutations that were located in the 5′ region of the gene and were predicted to introduce a premature translational termination codon (PTC).…”
Section: Introductionsupporting
confidence: 72%
“…This finding was confirmed by transient overexpression of a c.34C > T-containing expression vector in a cell line without endogenous SMARCB1 protein and subsequent detection of the shortened SMARCB1 protein by Western blotting. Similar overexpression experiments indicated that the mutations c.30delC, c.38delA, and c.46A > T also lead to truncated SMARCB1 proteins which may well be partially functional (Hulsebos et al 2014a). …”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations